The new perspective of the european neighbourhood policy for the black sea region - Elmas, Tuğba (My University, 2009)
Bu tezin amacı, Karedeniz Sinerjisi’nin, Avrupa Komşuluk Politikası’nın Karadeniz Bölgesi’ne yönelik eksikliklerini tamamlamak ve bu politikanın Kardeniz Bölgesi’nde başarısız olmasını önlemek amacıyla geliştirilen bir strateji olduğunu kanıtlamaktır. Avrupa Komşuluk Politikası, Avrupa Birliği’nin doğusundaki ve Akdeniz Bölgesi’ndeki komşularını aynı politika çerçevesinde ele aldığı için, bu bölgelere özgü problemlerle müdahale etmekte ve onlara cözüm sunmaktada etkili olamamıştır. Ancak, Karadeniz Bölgesi Avrupa güvenliğinin sağlanması açısından büyük bir role sahiptir. Ayrıca, bölgenin, Rusya’dan bağımsız alternatif enerji kaynakları sunması ve enerjinin Avrupa’ya taşınmasındaki önemi, Avrupa Birliği’nin bölgeye yönelik etkili bir politika oluşturulması arayışına girmesine neden olmuştur ve bunun sonucu olarak Karadeniz Sinerjisi ortaya çıkmıştır. Karadeniz Sinerjisi’nin bölge ülkelerinin ihtiyaç ve beklentilerine etkin bir şekilde cevap verebileceği düşünülmüştür. Bu sayede, Avrupa Birliği, hem Karadeniz Bölgesi ülkelerinin Birliğin kuralları, normları ve standartlarıyla uyumlu olarak hareket etmelerini garantilemek istemiştir hem de kendisine etkili bir dış politika aktörü imajı kazandırmayı hedeflemiştir. Çalışmanın sonucunda şu tespitlere ulaşılmıştır: İlk olarak, Avrupa Komşuluk Politikası, Karadeniz Bölgesi’ndeki problemlere ve güvenlik tehditlerine müdahale etmekte başarısız olmuştur ve bu nedenle bölgedeki ülkeleri hayal kırıklığına uğratmıştır. İkinci olarak, Karadeniz Bölgesi, stratejik konumu nedeni ile, Avrupa Birliği dış politikasında çok önemli bir yere sahiptir ve Birlik bölge ülkeleri ile arasındaki ilişkilerden daha somut getirileriler alabilmek için yeni bir yapılanmaya ihtiyaç duymuştur. Son olarak, Karadeniz Sinerjisi Avrupa Komşuluk Politikası’nın eksiklerini ve Karadeniz bölgesine yönelik zayıflıklarını göz önünde bulundurarak oluşturulmuştur ancak yine de beklentileri karşılayıp karşılayamayacağı şüphelidir.

In this thesis, it is argued that the Black Sea Synergy (BSS) is developed in order to eliminate the deficiencies and therefore prevent the failure of the European Neighbourhood Policy (ENP). Because the ENP deals with both the eastern and Mediterranean neighbours of the European Union (EU) within the same policy framework, it cannot effectively address their specific regional problems. However, the strategic importance of the Black Sea Region (BSR) in providing European security and especially its significant role in supply and transportation of non-Russian energy sources pushed the EU to develop the BSS that could enable it to overcome many regional security threats and benefit from various opportunities. Moreover, the BSS is also believed to respond the demands and expectations of the BSR countries more efficiently. So, through the launch of the policy, the EU aimed to ensure that the countries of the BSR would keep on complying with the EU norms, standards and further their reform processes. By this way, the Union could also improve its image as an influential foreign policy actor. The study concludes that, first; the ENP could not address the specific problems and security threats in the BSR and it created disappointment on the part of the BSR countries. Second, because the BSR has occupied an important place in the EU’s foreign policy agenda, due to its strategic importance; the EU needed to provide a new incentive in its relations with the BSR countries in order to obtain tangible results from this relationship. Third, although the BSS was established through taking into consideration the shortcomings of the ENP, it is doubtful whether it could become successful in fulfilling its declared promises. TABLE OF CONTENTS LIST OF ABBREVIATIONS V INTRODUCTION 1 I. THE EUROPEAN NEIGHBOURHOOD POLICY 13 1.1. A Historiacal Overview of the EU/ EC’s Approach to its Neighbourhood 13 1.2. Underlying Reasons of the ENP 16 1.3. Emerging Agenda of the ENP 18 1.4. Objectives and Basic Tenets of the ENP 21 1.4. Instruments and Methods of the ENP 25 1.5.1. Country Reports 26 1.5.2. Action Plans 26 1.5.3. Progress Reports 27 1.5.4. European Neighbourhood and Partnership Instrument 28 1.6. Strengthening the ENP 29 1.7. Constraints to the ENP 32 II. THE BLACK SEA REGION AND THE EU INVOLVEMENT 36 2.1 The Black Sea Region 36 2.1.1. Challenges 37 2.1.2. Opportunities 39 2.2. Established Cooperation Structures in the Region 41 2.2.1. Black Sea Economic Cooperation 42 2.2.2. Other Cooperation Structures 46 2.3. EU Involvement in the Region 49 2.3.1. Early EU Initiatives 50 2.3.2. Current EU Presence in the Region 54 III. BLACK SEA SYNERGY 57 3.1. Rationale for the Synergy 57 3.2. Development of the Synergy and Key Features 62 3.3. Objectives and Main Cooperation Areas 66 3.4. Cooperation with the Regional Organizations 71 3.5. Report on the First Year Implementation of the Black Sea Synergy 74 CONCLUSION 79 REFERENCES 83
Keywords: Avrupa Birliği; Uluslararası İlişkiler